Ultrashort Peptide Self-Assembly: Front-Runners to Transport Drug and Gene Cargos - Gupta, Seema; Singh, Indu; Sharma, Ashwani K.; Kumar, Pradeep (Frontiers in Bioengineering and Biotechnology, 2020)
The translational therapies to promote interaction between cell and signal come with stringent eligibility criteria. The chemically defined, hierarchically organized and simpler yet blessed with robust intermolecular association, the peptides, are privileged to make the cut-off for sensing the cell-signal for biologics delivery and tissue engineering. The signature service and insoluble network formation of the peptide self-assemblies as hydrogels have drawn a spell of research activity among the scientists all around the globe in the past decades. The therapeutic peptide market players are anticipating promising growth opportunities due to the ample technological advancements in this field. The presence of the other organic moieties, enzyme substrates and well established protecting groups like Fmoc and Boc etc., bring the best of both worlds. Since the large sequences of peptides severely limit the purification and their isolation, this article reviews the account of last five years’ efforts on novel approaches for formulation and development of single molecule amino acids, ultra-short peptide self-assemblies (di and tri peptides only) and their derivatives as drug/gene carriers and tissue-engineering systems.